TikNep: content analysis of Nepali TikTok users using natural language processing - Dhakal, Aakar; Lamichhane, Ashok; Jha, Aatish Kumar; Singh, Mukund Prasad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.